Universal occurrence of antibodies to tubercle bacilli in sera from non-tuberculous and tuberculous individuals - Bardana, E. J. (1973)
Studies were carried out to detect and quantitate humoral antibodies to components derived from Mycobacterium tuberculosis. Using both quantitative and qualitative primary tests, binding was observed by all sera obtained from normal as well as from tuberculous subjects. There was a significant difference, however, in the amount of binding by sera from controls. There was a high incidence of both IgG and IgM antibodies in all sera. The universal occurrence of humoral antibodies demonstrated in this study suggests that most, if not all, persons have been sensitized to the tubercle bacillus to one degree or another. Evidence is presented that the immunogens involved may be derived from saprophytic and/or avirulent mycobacteria.